Characterizing safety, toxicity, and breast cancer risk reduction using a long-term fulvestrant eluting implant - Scott Thomas; Elysia Roche; Pujan Desai; Nela Pawlowska; Diana Bauer; David Gingrich; Emily Hsu; Amelia N. Deitchman; Fran Aweeka; Pamela N. Munster (Scientific Reports)
Abstract For individuals at high risk of developing breast cancer, interventions to mitigate this risk include surgical removal of their breasts and ovaries or five years treatment with the anti-estrogen tamoxifen or aromatase inhibitors. We hypothesized that a silicone based anti-estrogen-eluting implant placed within the breast would provide the risk reduction benefit of hormonal therapy, but without the adverse effects that limit compliance. To this end, we demonstrate that when placed adjacent to mammary tissue in the 7,12-dimethylbenz[a]anthracene-induced rat breast cancer model a fulvestrant-eluting implant delays breast cancer with minimal systemic exposure. Using adult female sheep, surgical placement of fulvestrant-eluting implants was safe and did not elicit significant breast tissue pathology when placed at the base of the udder for directed elution into the mammary tissue. At 30 days of elution, fulvestrant was found to penetrate mammary tissue forming a concentration gradient beyond 15 mm from the implant. Consistent with the small animal rat study, minimal systemic fulvestrant biodistribution was found. Together, these studies provide the proof of principle that a breast indwelling fulvestrant-eluting implant can reduce the risk of breast cancer and limit systemic exposure, while penetrating and distributing through breast tissue.